Dyadic Developmental Psychotherapy for children living with adoptive parents or special guardians: a longitudinal assessment of the impact on child and caregiver wellbeing outcomes. (June 2023) - Burch, Katy; Coombes, Lindsey; Macey, Ellie; Backinsell, Andy
Dyadic Developmental Psychotherapy (DDP) is a form of psychotherapy for families where children and young people have experienced early trauma or attachment disruption. This study used longitudinal survey data to understand the format of DDP as it is provided in England for children who are adopted or subject of a Special Guardianship Order (SGO), and to analyse the potential effects of DDP on standardised outcomes of child and caregiver wellbeing. Participants were 150 families who received DDP through funding from the Department for Education's Adoption Support Fund in England between 2018 and 2021. Adoptive parents and special guardians (caregivers) answered surveys at three timepoints; before therapy was provided (baseline), when therapy had ended (wave 2), and 6 months later (wave 3). Linear mixed modelling demonstrated significant improvements in child/young person difficulties in multiple subscales of the SDQ, including emotional difficulties and conduct problems, between baseline and wave 2. In the same time frame, similar improvements in caregiver wellbeing were also observed, as measured by the SWEMBS. These findings suggest an association between the provision of DDP and an improvement in child/young person and caregiver wellbeing on standardised measures, with these improvements maintained 6 months later. Implications and recommendations for future research to substantiate the findings are discussed.